Tracking of Scalpel Motions With an Inertial Measurement Unit System - Kabuye, Ernest; Hellebrekers, Tess; Majidi, Carmel; Cagan, Jonathan; Leduc, Philip (IEEE Sensors Journal, 2022)
Surgical planning to visualize a complete procedure before surgical intervention, paired with the advanced surgical techniques of a surgeon, has been shown to improve surgical outcomes. Efforts to improve surgical planning have included tracking real-time surgeon movements via surgical instruments in a confined body cavity space in the human body to enhance specific techniques when performing minimally invasive surgery. In this work, a surgical tool tracking approach is presented that leverages small scale electronics to enable real-time position capture for use in iterative surgical planning. By integrating a lightweight 9 degree-of-freedom Inertial Measurement Unit (IMU), our system captures both spatial and temporal information of the surgical tool without requiring a direct line-of-sight. The IMU is printed on a flexible film and attached to and integrated with a surgical tool demonstrating its tracking capabilities. Data from the IMU is analyzed to determine the full range of motion during angular displacement for measurement and tracking. The results show an accuracy of 2.2 0 , 2.9 0 and 3.1 0 of the full range of motion of the X (Yaw), Y (Roll) and Z (Pitch) Euler angle coordinate system respectively demonstrating the potential for surgical tool tracking measurement without the need for a direct line of sight and with future impact including flexible electronics and motion tracking. This work will be helpful in a diversity of fields including surgery, surgical training, biomaterials, and motion tracking.
Keywords: Inertial Measurement Unit System; Tracking; Scalpel Motions